Menjadi Muslim Sejati di Era Digital Menggabungkan Nilai-Nilai Islam dengan Kehidupan Modern - Hadi, Mahrus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2025)
This article seeks to examine the difficulties encountered in striving to be a devout Muslim within the context of an evolving modern society. It emphasizes the transition from traditional norms to the digital age and outlines the distinct challenges Muslims face today in preserving their faith and upholding Islamic principles. Technology, on the one hand, enhances information accessibility and broadens the scope of social connectivity, but on the other hand, exposure to negative content and consumerist lifestyles has also increased. This study aims to analyze how Muslims can integrate Islamic values ​​into their digital lives, and to examine the obstacles and prospects encountered in the pursuit of authentic Islamic practice in contemporary times. The rapid development of social media has changed the way humans interact and access information. This study aims to understand how the use of social media affects the daily worship practices of Muslims, especially the younger generation. This study aims to identify the types of social media content most frequently consumed by Muslim youth; (2) analyze the influence of this content on motivation and daily worship practices; and (3) identify effective strategies for utilizing social media to improve the quality of worship.